Halo histories versus galaxy properties at z = 0 II: large-scale galactic conformity. Issue 1 (15th March 2018) - Tinker, Jeremy L; Hahn, ChangHoon; Mao, Yao-Yuan; Wetzel, Andrew R; Conroy, Charlie
Abstract: Using group catalogues from the Sloan Digital Sky Survey (SDSS) Data Release 7, we measure galactic conformity in the local universe. We measure the quenched fraction of neighbour galaxies around isolated primary galaxies, dividing the isolated sample into star-forming and quiescent objects. We restrict our measurements to scales >1 Mpc to probe the correlations between halo formation histories. Over the stellar mass range 10 9.7 ≤ M * /M⊙ ≤ 10 10.9, we find minimal evidence for conformity. We further compare these data to predictions of the halo age-matching model, in which the oldest galaxies are associated with the oldest haloes. For models with strong correlations between halo and stellar age, the conformity is too large to be consistent with the data. Weaker implementations of the age-matching model would not produce a detectable signal in SDSS data. We reproduce the results of Kauffmann et al., in which the star formation rates of neighbour galaxies are reduced around primary galaxies when the primaries are low star formers. However, we find this result is mainly driven by contamination in the isolation criterion; when removing the small fraction of satellite galaxies in the sample, the conformity signal largely goes away. Lastly, we show that small conformity signals, i.e. 2–5 per cent differences in the quenched fractions of neighbour galaxies, can be produced by mechanisms other than halo assembly bias. For example, if passive galaxies occupy more massive haloes than star-forming galaxies of the same stellar mass, a conformity signal that is consistent with recent measurements from PRIMUS (Berti et al.) can be produced.